Measurement of dissolved CO2 transport by snowmelt runoff in paddy fields - KOMINAMI, Yasuhiro (Journal of Agricultural Meteorology, 2011)
The quantity of CO2 carried away by snowmelt during the thawing of a deposited snow layer was measured in an area subject to seasonal accumulation of snow. The concentration of dissolved CO2 was measured in snowmelt discharged from the outlet of a paddy field with heavy clay soil in Joetsu City, Niigata Prefecture, Japan. Samples were taken every few hours over a period of three days. The CO2 flux Fwater transported by the snowmelt was estimated from changes in the concentration of dissolved CO2, with the CO2 concentration continuously measured at the bottom of the deposited snow layer, and the quantity of snowmelt estimated from heat balance measurements. The ratio of the CO2 concentration, Csnow, to that dissolved in the snowmelt, Cwater, gradually decreased as the quantity of snow melted per unit time increased. Therefore, assuming this ratio to be proportional to the inverse of the snowmelt flow speed, a regression was carried out, based on the fact the flow speed is proportional to the quantity of melted snow per unit time raised to a power of 2/3. To assess the validity of the estimated Fwater, we studied the balance of CO2 in the deposited snow layer by using the CO2 store in the deposited snow. The quantity value of the soil respiration flux estimated from the balance of CO2 in the deposited snow layer was close to the average soil respiration flux during the snow-covered period estimated by the CO2 concentration gradient and the volume fraction of air in the snow layer previously deposited in the same paddy field.